Soft issues in IS Projects: lessons from a Not-for-Profit in New Zealand - Shimmin, Rory (Auckland University of Technology, 2009)
Taylor and DaCosta (1999) explored how Soft System Methodology (SSM), having been practiced predominantly in the large organisation sector, could be successfully practiced in a small to medium enterprise (SME). This dissertation is a case study on how SSM can be used within the Not-for-Profit sector in New Zealand. The researcher conducted the SSM process, collected resulting models and requirements, documentation and conducted four interviews with participants. By dealing with a problem situation, rather than looking for an immediate technological solution, when exploring information system requirements, SSM can be used advantageously whether in a Not-for-Profit or SME. The Not-for-Profit culture encourages people collaboration and as SSM is predominantly a people oriented process, it can be shown that this was a suitable process for investigating information system requirements in this Not-for-Profit New Zealand organisation, resulting in several benefits. This study concludes that investigating Not-for-Profit’s information system requirements should not be that different to those of a similar sized SME and therefore, SSM should be a suitable process for Not-for-Profits.
Keywords: Soft System Methodology; Soft; Information System; SSM; Case study; NFP; SME; Not-for-Profit